2018
DOI: 10.1261/rna.067777.118
|View full text |Cite
|
Sign up to set email alerts
|

The binding of Class II sRNA MgrR to two different sites on matchmaker protein Hfq enables efficient competition for Hfq and annealing to regulated mRNAs

Abstract: MgrR is an Hfq-dependent sRNA, whose transcription is controlled by the level of Mg ions in MgrR belongs to Class II sRNAs because its stability in the cell is affected by mutations in Hfq differently than canonical, Class I sRNAs. Here, we examined the effect of mutations in RNA binding sites of Hfq on the kinetics of the annealing of MgrR to two different target mRNAs, and , by global data fitting of the reaction kinetics monitored by gel electrophoresis of intermediates and products. The data showed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
4
16
1
Order By: Relevance
“…An interaction between RelA-like protein and RNA was documented previously for RelQ (40). The authors showed that the small alarmone synthetase RelQ from the Gram- (17,24,(45)(46)(47). Also, ChiX, MgrR and DsrA that lack the GGAG sequence were reported to be better competitors for binding Hfq than RyhB, McaS or CyaR sRNAs (46).…”
Section: Rela Ggag Srna Binding and (P)ppgpp Productions Are Mutuallymentioning
confidence: 66%
See 1 more Smart Citation
“…An interaction between RelA-like protein and RNA was documented previously for RelQ (40). The authors showed that the small alarmone synthetase RelQ from the Gram- (17,24,(45)(46)(47). Also, ChiX, MgrR and DsrA that lack the GGAG sequence were reported to be better competitors for binding Hfq than RyhB, McaS or CyaR sRNAs (46).…”
Section: Rela Ggag Srna Binding and (P)ppgpp Productions Are Mutuallymentioning
confidence: 66%
“…The authors showed that the small alarmone synthetase RelQ from the Gram- (17,24,(45)(46)(47). Also, ChiX, MgrR and DsrA that lack the GGAG sequence were reported to be better competitors for binding Hfq than RyhB, McaS or CyaR sRNAs (46). Interestingly, both MgrR and ChiX carry in addition to poly(U) tail three and four ARN motifs, respectively (25,45).…”
Section: Rela Ggag Srna Binding and (P)ppgpp Productions Are Mutuallymentioning
confidence: 99%
“…1E, F). This approach was used before to show that ChiX and MgrR sRNAs bind both the distal face and the proximal face of Hfq [38, 39], while RybB sRNA binds only to the proximal face of Hfq, in agreement with previous studies [29, 31]. Our data showed that both AgvB and 3′ETS leuZ easily induce the dissociation of A 27 -Hfq complexes, with low IC 50 values (3.2 ± 1.4 nM and 2.8 ± 0.35 nM, respectively, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4D). In this way GcvB resembles mRNAs targeted by class II sRNAs, such as eptB or chiP , for which the rim mutant also did not stimulate annealing (Kwiatkowska et al, 2018). Like class II mRNAs, the sequence of GcvB is rich in uridines which mediate the interactions with the Hfq rim [28, 29, 46].…”
Section: Discussionmentioning
confidence: 99%
“…8B) (9,12). While Hfq can bind A-rich sequences, for example ARN motifs, in some of its RNA ligands, these sequences are located either in mRNA 5ʹ-UTRs (35)(36)(37) or far upstream of intrinsic terminators in a subgroup of Hfq-specific sRNAs, called Class II sRNAs (40)(41)(42). However, in the dominant subgroup of Hfq-binding sRNAs, called Class I sRNAs, the Hfq-binding module consists of a U-rich motif just upstream of the intrinsic terminator, which is followed by a long 3ʹ oligoUtail (39,54).…”
Section: A Terminator Adjacent A-rich Motif Serves As a Negative Detementioning
confidence: 99%